EXPLORING SELF-DIRECTED LEARNING IN PRACTICAL CLASS FOR HOSPITALITY STUDENTS - Abdul Razak, Roshita; Eshaby Mustafa; Azman, Fara Ashikin; Ramly, Nur Zamahuri (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The Malaysia Education Development Plan 2015-2025 (Higher Education) aims to strengthen Technical and Vocational Education and Training (TVET) to meet the demands of the industry by producing skilled workers. It is crucial for TVET students to enhance their skills through high-quality practical training. This study aims to investigate the self-directed learning as learning styles and the achievement of practical hospitality courses among hospitality students in community college in the northern part of peninsular Malaysia. This study proposes to apply the Kolb’s Learning Style. This quantitative study utilizes a survey method, with preliminary study involving 30 students and the actual sample of 136 participants comprising students from semester two and semester three at the identified Community Colleges using Proportionate Stratified Random Sampling technique. The preliminary collected data were analyzed using the Statistical Package for Social Science (SPSS) version 27.0. The findings of this study are expected to provide a better understanding of learning styles and self -directed learning on academic achievement in the context of TVET among hospitality students at Community Colleges.